Operational efficiency of timber loading and unloading in Sapulut, Sabah - Aziz, Mohammad Azhar (2019)
Good transportation and integrated infrastructure are required to realize adequate economic return to make processing a diverse log supply feasible (John et al., 2004). Loading and unloading is one of the important components in forest transportation. Loading process is a mechanism that connects between skidding and hauling operation. The main issues is regarding to low productivity by loader log grapple that may cause delay in harvesting process. The objective of this study was to measure time and volume of tree carry loader tractor operation in forest. Second, to analyze the relationship between time, volume and distance of carry loader tractor operation and third, to determine the efficiency loading and unloading by loader tractor in Sapulut Forest Reserve, Tibow, Sabah. The study was conducted in forest undergo harvesting operation in Sapulut Tibow, Sabah. Data collected based on distance and time, time and productivity, and last but not least data on distance and productivity. Productivity is the main target that should achieve in a certain harvesting process. To get the optimum rate of productivity, time and volume of log carried by loader log grapple should be considered. Volume of log per trip for both process of loading and unloading should be maintain between 54 m3 to 56 m3 and the total time at 0.8 to 0.9 hours that will come out the highest rate of productivity which between 55 to 57. In this study, the result shows the process of loading handled by loader log grapple take the total time 3.13 hours to complete 5 trips per day. The capability of experienced driver can conduct about 8 to 10 trips or more in one day which is equivalent to 400 m3 to 500 m3. While for unloading process an experienced driver can conduct about 11 to 15 trips or more in one day which is equivalent to 400 m3 to 500 m3. Furthermore, total distance for loading and unloading process from log pond to lorry influenced the effectiveness of time and productivity even slightly different on distance. The relationship between time, volume and productivity had been discussed in this study. The result from this study can be used for improvement on environment disturbance and economical value for harvesting process in the future.